Efficacy evaluation of pulmonary hypertension therapy in patients with portal pulmonary hypertension: A systematic review and meta-analysis - Zhang, Ruihua; Li, Tengfei; Shao, Yueming; Bai, Wei; Wen, Xiaoyu (Frontiers in Pharmacology, 2022)
Objective: To determine the therapeutic effect of pulmonary arterial hypertension (PAH) agents for portal pulmonary hypertension (POPH). Design: Systematic review and meta-analysis. Background: POPH is a serious complication of end-stage liver disease with a low survival rate. Liver transplantation (LT) is an effective treatment. Due to the presence of POPH, some patients cannot undergo LT. After PAH treatment, patients with POPH can obtain good hemodynamics and cardiac function for LT, but there are no standard guidelines. Methods: Two independent researchers searched PubMed, EMBASE, Cochrane Library, and Web of Science for studies published from inception to September 27, 2022, focusing on the changes in hemodynamics and cardiac function in all patients with POPH to understand the effect of PAH treatment on the entire population of POPH patients. Among these, we specifically analyzed the changes in hemodynamics and cardiac function in moderate and severe POPH patients. After collecting the relevant data, a meta-analysis was carried out using the R program meta-package. Results: A total of 2775 literatures were retrieved, and 24 literatures were included. The results showed that in all POPH patients (n= 1,046), the following indicators were significantly improved with PAH agents: mPAP: (MD=-9.11 mmHg, P<0.0001); PVR: (MD=-239.33 dyn·s·cm-5, P<0.0001); CO: (MD=1.71 L/min, P<0.0001); cardiac index: (MD=0.87 L/(min·m2), P<0.0001); 6MWD: (MD=43.41 m, P<0.0001). In patients with moderate to severe POPH (n= 235), the following indicators improved significantly with PAH agents: mPAP (MD=-9.63 mmHg, P<0.0001); PVR (MD=-259.78 dyn·s·cm-5, P<0.0001); CO (MD=1.76 L/min, P<0.0001); Cardiac index: (MD=1.01 L/(min·m2), P=0.0027); 6MWD: (MD=61.30 m, P<0.0001). Conclusion: The application of PAH agents can improve cardiopulmonary hemodynamics and cardiac function in patients with POPH, especially in patients with moderate to severe POPH, and the above changes are more positive.